A "Post-Copenhagen" Analysis of China's Securitization of the Uyghur: A Counterproductive Securitization?. Issue 4 (2nd October 2021) - Baker-Beall, Christopher; Clark, Robert
ABSTRACT: This article adopts a post-Copenhagen approach to securitization theory in order to critically analyze the security policies developed by the People's Republic of China (PRC) that have targeted the Uyghur community in Xinjiang province. The article explores the relationship between the language of security and threat, which has been invoked by the PRC leadership, and its role in justifying every-day and exceptional security practices that have been enacted against the Uyghurs since the start of the 1990s. The article makes two important claims. First, the article argues that the securitization of the Uyghur has proved counter-productive, potentially creating the very security threat that the securitization of an issue is supposed to prevent. Second, the article suggests that the role of various audiences, both domestic and international, even in an authoritarian or illiberal state like China, play a key role in the securitization process and the legitimization of the security measures that have been enacted against the Uyghur community.